Ginsenoside compound K inhibits growth of lung cancer cells via HIF-1Î±-mediated glucose metabolism - Chen, Hua-fei; Wu, Li-xin; Li, Xiao-feng; Zhu, You-cai; Wang, Wen-xian; Xu, Chun-wei; Huang, Zhang-zhou; Du, Kai-qi (Cellular and Molecular Biology, 2019)
Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related deaths. Compound K, an active metabolite of ginsenosides, is reported to exhibit anti-cancer property in various types of human malignancies. The present study investigated the role of compound K on glucose metabolism in NSCLC cells and its underlying mechanism. Our study found that compound K dose-dependently inhibited the cell viability of NSCLC cells. Moreover, administration with compound K decreased glucose uptake and lactate secretion under normoxic and hypoxic conditions. Consistently, the expression of key enzymes (HK II, PDK1 and LDHA) involved in glucose metabolism were inhibited in compound K-treated tumor cells. In addition, compound K inhibited the expression of HIF-1Î± and its downstream gene GLUT1. On the contrary, overexpression of HIF-1Î± elevated metabolic reactions and partly attenuated the inhibitory role of compound K on NSCLC cell growth. These results demonstrate that compound K suppresses NSCLC cell growth via HIF-1Î± mediated metabolic alteration, contributing to novel anticancer therapy by targeting glucose metabolism.